(untitled) (Bangladesh Journal of Botany, 2024)
The present investigation was conducted to assess functional qualities of water chestnut enriched flaxseed nutritional laddu. The quality evaluation of the nutritional laddu was done up to 20 days of storage. These laddu contained appreciable amounts of crude protein (24.22%), crude fat (28.25%), crude fibre (9.95%) and total ash (4.86%). All of these decreased during storage periods in all the treatments. The maximum L* value (53.133) was found in T6 (20% Flaxseed + 30% Water chestnut + 45% Jaggery + 3% Ginger + 2% Dry fruit) at 20 days and minimum (38.170) in T0 (50% Flaxseed + 45% Jaggery + 3% Ginger + 2% Dry fruit) at 0 day of storage period. The highest total ash was found in T6 (5.530) at 0 day and lowest in T0 (3.100) at 20 days. It was concluded that up to 30 % water chestnut can be incorporated in flaxseed laddu to obtain best overall acceptability. Bangladesh J. Bot. 53(3): 561-566, 2024 (September)